Evaluasi Kinerja Media Sosial Instgram Dalam Menyebarkan Informasi Studi Kasus : Akun Instagram Universitas Amikom Purwokerto - Lailatur Rochmah; Kusumas Astri Anggraeni; Farah Fadhilah; Ririt Farihatul Kamilah; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Information technology has changed the way educational institutions interact. Instagram, one of the visual-based social media platforms, has become a strategically used platform to create image, increase interaction, and disseminate information. Instagram is a tool used by Amikom Purwokerto University to disseminate information, both academic and non-academic, to students and the general public. However, problems such as unattractive format, inconsistent accuracy, and suboptimal delivery speed have been faced by the campus. The End-User Computing Satisfaction (EUCS) method was used in this study to evaluate the performance of Amikom Purwokerto University's Instagram account. Content, accuracy, format, ease of use, and timeliness are the five dimensions used to assess. The results showed an overall good level of satisfaction; the content dimension had the highest mean score (3.86), while the timeliness dimension had the lowest mean score (3.46).In this study, the researchers found that social media account managers at Amikom Purwokerto University can use strategic recommendations to improve the effectiveness of information dissemination. The findings can also be used as a reference for other educational institutions to use social media as a more interactive and responsive communication tool.